The relation between fracture activity and bone healing with special reference to the early healing phase – A preclinical study. Issue 1 (January 2021) - Windolf, Markus; Ernst, Manuela; Schwyn, Ronald; Arens, Daniel; Zeiter, Stephan
Highlights: In a pre-clinical study, an instrumented bone fixator allowed controlled and continuous assessment of fracture activity as potentially influential factor for fracture healing. A strong and significant correlation was found between fracture activity in the direct postoperative phase and the strength of the healed bone. Findings support the concept of early patient mobilization to improve the clinical outcome. However, results need to be validated in a clinical setting. Abstract: Background: Fracture healing outcome is to a great extent steered by the mechanical environment. The importance of early phase mechanical fracture stimulation is still controversially discussed, both clinically and scientifically. Furthermore, the role of fracture activity, defined as the number of stimulatory events per time, is particularly for the direct postoperative phase unknown. Methods: Tibial defects of seven Swiss mountain sheep were stabilized with a dynamizable bone fixator, which allowed for defined interfragmentary motion by limiting the maximum axial displacement. The fixator was further equipped with a telemetric measuring unit to continuously log all occurring displacement events above a predefined amplitude threshold over an 8-weeks observation period. Callus size was measured over time from X-rays. Ultimate torsional strength of the healed defects was assessed after euthanasia. Results: One animal had to be excluded from the experiment due to technical reasons. The remaining six animals exhibited consistently the highest fracture activity in week 1 post-operation with 6′029 displacement events per week for the animal with the lowest activity and 21′866 events per week for the most active animal. Afterwards fracture activity gradually decreased over time. Strong and significant correlations were found for fracture activity in week 1 and 2 with torsional strength of the healed bone ( R  ≥ 0.881, p  ≤ 0.02). No significant correlations were observed at later timepoints. Fracture activity in week 1 and 2 also correlated strongly with the maximum callus area as measured from X-rays ( R  ≥ 0.846, p  ≤ 0.034). Conclusions: The data demonstrates a positive effect of, within limits, frequent fracture stimulation on bone healing and suggests the importance of the mechanical environment in the direct post-operative healing phase. Clinically, the findings may advocate for the concept of direct post-operative weight bearing. This, however, requires clinical validation and must be considered within the full clinical context including the risk for fixation failure from overloading.